Structural Characterization of Carbon Nanomaterial Film In Situ Synthesized on Various Bulk Metals - J. Y. Xu; R. Yang; Z. Z. Fan; X. C. Lei (Journal of Spectroscopy)
Carbon nanofiber films were prepared via a simple chemical vapor deposition (CVD) method on various bulk metal substrates including bulk 316 L stainless steel, pure cobalt, and pure nickel treated by surface mechanical attrition treatment (SMAT). The microstructures of the carbon nanomaterial film were studied by SEM, TEM, XRD, and Raman spectroscopy. In this paper, bulk metallic materials treated by SMAT served as substrates as well as catalysts for carbon nanomaterial film formation. The results indicate that the carbon nanofiber films are formed concerning the catalytic effects of the refined metallic particles during CVD on the surface of SMAT-treated bulk metal substrates. However, distinguished morphologies of carbon nanomaterial film are displayed in the case of the diverse bulk metal substrates.